The Traffic Development of The Republic of Croatia within Europe in the 21 51 Century - Malić, Adolf; Badanjak, Dragan; Stipetić, Antun (Promet - Traffic&Transportation, 2012)
The paper deals with the prospective development of moderntransport technologies for 2Jih century as a precondition forintegration of Croatia with Europe. By its geographical position,Croatia is an eminently European country. Her transportinfrastructure and technological transp01t solutions present todaysignificant hindrance to its integration with Europe.The Transrapid railway system is a novel technologicaltransport form that could be developed in Croatia, within theEuropean Transrapid network. Fwthermore, Croatia has greatexpectations in the development of air transport even by airbuses for transporting cargo and passengers. Special attentionwill be paid to organising high-speed suburban traffic inZagreb, based on the railway.